The Development of Selective Copying: Children's Learning From an Expert Versus Their Mother. Issue 6 (29th December 2016) - Lucas, Amanda J.; Burdett, Emily R. R.; Burgess, Vanessa; Wood, Lara A.; McGuigan, Nicola; Harris, Paul L.; Whiten, Andrew
Abstract : This study tested the prediction that, with age, children should rely less on familiarity and more on expertise in their selective social learning. Experiment 1 ( N  = 50) found that 5‐ to 6‐year‐olds copied the technique their mother used to extract a prize from a novel puzzle box, in preference to both a stranger and an established expert. This bias occurred despite children acknowledging the expert model's superior capability. Experiment 2 ( N  = 50) demonstrated a shift in 7‐ to 8‐year‐olds toward copying the expert. Children aged 9–10 years did not copy according to a model bias. The findings of a follow‐up study ( N  = 30) confirmed that, instead, they prioritized their own—partially flawed—causal understanding of the puzzle box.